A Study of National Physician Organizations’ Efforts to Reduce Racial and Ethnic Health Disparities in the United States - Peek, Monica E. (2012)
PURPOSE: To characterize national physician organizations’ efforts to reduce health disparities and identify organizational characteristics associated with such efforts. METHOD: This cross-sectional study was conducted between September 2009 and June 2010. The authors used two-sample t tests and chi-square tests to compare the proportion of organizations with disparity-reducing activities between different organizational types (e.g., primary care versus subspecialty organizations, small [<1,000 members] versus large [>5,000 members]). Inclusion criteria required physician organizations to be (1) focused on physicians, (2) national in scope, and (3) membership based. RESULTS: The number of activities per organization ranged from 0 to 22. Approximately half (53%) of organizations had 0 or 1 disparity-reducing activities. Organiza-tional characteristics associated with having at least 1 disparity-reducing effort included membership size (88% of large groups versus 58% of small groups had at least 1 activity; P = .004) and the presence of a health disparities committee (95% versus 59%; P < .001). Primary care (versus subspecialty) organizations and racial/ethnic minority physician organizations were more likely to have disparity-reducing efforts, although findings were not statistically significant. Common themes addressed by activities were health care access, health care disparities, workforce diversity, and language barriers. Common strategies included education of physicians/trainees and patients/general public, position statements, and advocacy. CONCLUSIONS: Despite the national priority to eliminate health disparities, more than half of national physician organizations are doing little to address this problem. Primary care and minority physician organizations, and those with disparities committees, may provide leadership to extend the scope of disparity-reduction efforts.